2018
DOI: 10.1038/s41598-018-27805-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that thermal selection shapes mitochondrial genome evolution

Abstract: Mitochondria are essential organelles, found within eukaryotic cells, which contain their own DNA. Mitochondrial DNA (mtDNA) has traditionally been used in population genetic and biogeographic studies as a maternally-inherited and evolutionary-neutral genetic marker. However, it is now clear that polymorphisms within the mtDNA sequence are routinely non-neutral, and furthermore several studies have suggested that such mtDNA polymorphisms are also sensitive to thermal selection. These observations led to the fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 82 publications
1
45
0
Order By: Relevance
“…Through whole mitochondrial genome sequencing, we found variation in the number of tandem repeats in the control region in two samples, although this variation on its own did not seem to be strongly associated with haplotype fitness. However, our overall findings add to evidence that synonymous substitutions or changes in noncoding regions could affect mitochondrial function (Camus et al, ; Lajbner et al, ).…”
Section: Discussionsupporting
confidence: 79%
“…Through whole mitochondrial genome sequencing, we found variation in the number of tandem repeats in the control region in two samples, although this variation on its own did not seem to be strongly associated with haplotype fitness. However, our overall findings add to evidence that synonymous substitutions or changes in noncoding regions could affect mitochondrial function (Camus et al, ; Lajbner et al, ).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, body temperature variation is associated with reduced fitness, with more extreme daily fluctuations correlated with reduced reproduction in wild mammal populations (Maloney, Marsh, McLeod, & Fuller, ). Cells recognize environmental fluctuations through sophisticated signaling pathways and hence stress directly affects the cellular integrity, function, and morphology (Rabouille & Alberti, ) and shapes mitochondrial genome evolution (Lajbner et al, ). The maintenance of homeothermy during heat stress in SCB was achieved primarily by heterothermy.…”
Section: Discussionmentioning
confidence: 99%
“…The phylogeny revealed that Vechur and Wayanad clustered in the Indicus 1 haplotype (I1), while Kasargode clustered in the Indicus 2 (I2) haplotype, showing a convergent evolution of dwarf size in response to high heat and humidity in cattle breeds in different regions (Taye et al, ). The mitochondrial genome of dwarf cattle might have evolved through selection under heat stress (Lajbner et al, ). In domestic cattle, dwarfing and tolerance is evolutionarily defined by functional traits developed through maternal founder effect and adaptation to warm environments (Lenstra et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations